2014
DOI: 10.1016/j.fgb.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

MAT gene idiomorphs suggest a heterothallic sexual cycle in a predominantly asexual and important pine pathogen

Abstract: Diplodia pinea (= Sphaeropsis sapinea) is a well-known and economically important latent pathogen of Pinus spp. in many parts of the world. Despite intensive scrutiny, its sexual state has never been observed and the fungus has thus been considered exclusively asexual. It was, therefore, surprising that a recent population genetics study showed high genotypic diversity and random association of alleles in a number of populations, suggesting that the pathogen has a cryptic sexual stage. Using the genome sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 57 publications
4
50
0
Order By: Relevance
“…However, results of a population genetics study of the fungus considering the lack of linkage disequilibrium amongst alleles, as well as the generally high genotypic diversity, proposed that a cryptic sexual state probably exists for this fungus (Bihon et al 2012). In support of this conclusion, a recent study of mating type loci showed various populations of D. sapinea contained the two mating type idiomorphs in more or less equal frequency, which is indicative of a heterothallic sexual cycle (Bihon et al 2014). …”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, results of a population genetics study of the fungus considering the lack of linkage disequilibrium amongst alleles, as well as the generally high genotypic diversity, proposed that a cryptic sexual state probably exists for this fungus (Bihon et al 2012). In support of this conclusion, a recent study of mating type loci showed various populations of D. sapinea contained the two mating type idiomorphs in more or less equal frequency, which is indicative of a heterothallic sexual cycle (Bihon et al 2014). …”
Section: Introductionmentioning
confidence: 76%
“…Diplodia sapinea has similar genome size to Fusarium graminearum (36.1 Mb), but with a greater number of genes (11640) (Cuomo et al 2007). The genome sequence of D. sapinea species has already made the characterisation of the MAT locus possible (Bihon et al 2014) and access to this genome will no doubt facilitate further research on this important tree pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the MAT1-2 idiomorph typically harbours the MAT1-2-1 gene, encoding an HMG box protein . Although this is generally the only gene present at this locus, other genes including the MAT1-2-2, MAT1-2-3, MAT1-2-4 and MAT1-2-5 genes have also been described and are named in the order of their discovery (BIHON et al 2014;MANDEL et al 2007;MARTIN et al 2011;PÖGGELER and KÜCK 2000). The expression of genes from both these idiomorphs is typically required for the completion of a sexual cycle (COPPIN et al 1997) and thus, fungal mating systems can be classified based on the structure and gene content of the MAT locus.…”
Section: Introductionmentioning
confidence: 99%
“…This ease of access has made it feasible to rapidly compare multiple genomes and has led to major improvements in our understanding of the lifestyles, niche specialisation, and emergence of fungal phytopathogens (Gardiner et al 2012;Klosterman et al 2011;Thynne et al 2015). Genomes of Botryosphaeriaceae family are now being exploited to identify basic biological processes such as homothalism vs. heterothallism, which once took years of careful experiments to correctly assign (Islam et al (2012); Blanco-Ulate et al (2013); Bihon et al (2014)). For example, Bihon et al (2014) used the genome sequences of Diplodia pinea to describe the mating type idiomorphs for this species, and in doing so described a novel putative MAT gene, characterised as MAT1-2-5 (Bihon et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Genomes of Botryosphaeriaceae family are now being exploited to identify basic biological processes such as homothalism vs. heterothallism, which once took years of careful experiments to correctly assign (Islam et al (2012); Blanco-Ulate et al (2013); Bihon et al (2014)). For example, Bihon et al (2014) used the genome sequences of Diplodia pinea to describe the mating type idiomorphs for this species, and in doing so described a novel putative MAT gene, characterised as MAT1-2-5 (Bihon et al 2014).…”
Section: Discussionmentioning
confidence: 99%